(untitled) (Research, Society and Development, 2020)
This study aims to verify the orofacial findings of congenital generalized lipodystrophy (LGC) in patients diagnosed with this condition. This is a systematic review of the literature, carried out in accordance with the PubMed, Web of Science and Scopus databases. 14 studies published in the last 15 years that addressed the orofacial clinical findings of LGC were included. LGC is a rare autosomal recessive condition, presenting a wide variety of manifestations that affect the oral and facial regions. The main orofacial findings identified were prognathism, absence of facial subcutaneous fat, prominent frontal and supraorbital protrusions, low frontal hairline, triangular face, facial hirsutism, macroglossia, labial hypertrophy, abnormal dental morphology, dental caries, tooth absences, diastemas and crowding dental. The results indicate that LGC can cause significant orofacial changes in individuals, and it is important that these patients are monitored by a multidisciplinary health team, and that these professionals have knowledge based on scientific evidence regarding these clinical findings, to offer a better prognosis for these patients.